Sv-SnS2 material based on glucose reduction as well as preparation method and application of Sv-SnS2 material
The glucose reduction method increases the concentration of S vacancy in SnS2 material and improves its electronic structure, solving the problem of insufficient response and recovery performance of SnS2 material at room temperature, and realizing the preparation of a high-performance ammonia sensor.
Patent Information
- Application Number
- CN202411827175.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing SnS2 materials are difficult to achieve rapid response and recovery at room temperature, and are insufficient in humidity resistance, which limits their application in ammonia sensors.
The concentration of S vacancy in SnS2 material is increased by glucose reduction method, and its electronic structure is improved, thereby improving the response and recovery performance of the gas sensor. The method includes two hydrothermal reactions, the first reaction to produce SnS2 powder, and the second reaction to add glucose and cationic surfactant to form Sv-SnS2 material.
It realizes rapid response and recovery of SnS2 materials at room temperature, improves the detection performance of ammonia, and has low process cost and simple operation, making it suitable for large-scale production.
Smart Images

Figure CN119569108A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional material preparation, and specifically relates to a Sv-SnS2 material based on glucose reduction, and a preparation method and application thereof. Background Art
[0002] SnS2 is a kind of two-dimensional transition metal sulfide (TMDs), which is a popular two-dimensional material now. SnS2 is a narrow bandgap interlayer structure TMDs material with a large specific surface area and high surface activity. It has been widely studied in the fields of photodetectors, catalysis and gas sensing. However, gas sensors based on SnS2 are still challenging in room temperature sensing due to their own high baseline resistance and difficulty in recovery at room temperature. In order to make it adapt to the conditions of low-temperature sensing, people have carried out morphology regulation, heterostructure construction and precious metal modification. However, most of these gas sensors based on SnS2 need to work in high temperature environments. Defect engineering is an effective strategy to improve the properties of the material itself. Vacancies can increase the number of unsaturated coordinated electrons and unsaturated coordinated active sites, reduce the energy barrier of gas molecule adsorption, and are an effective strategy to achieve room temperature sensing.
[0003] Ammonia, as an alkaline gas that regulates atmospheric balance, is also widely used in electronics, food processing, and chemistry. However, the current generation of ammonia sensors is plagued by several limitations, including slow response rate, challenges in achieving rapid recovery at ambient temperature, and insufficient humidity resistance, which have imposed significant restrictions on their practical applications. Therefore, exploring high-performance ammonia sensors with fast response at room temperature and resistance to high humidity is of great practical significance for carbon neutrality and disease early warning.
[0004] For a material, factors such as the difficulty of the preparation process, cost issues, and yield rate are necessary conditions to determine whether it can be mass-produced, and also determine whether the material can be widely used. However, so far, the defect control methods reported for SnS2 materials are relatively harsh, with disadvantages such as high cost, high operating requirements, and insufficient control. The control method of this study has largely solved these shortcomings and accelerated the development speed of SnS2 from laboratory to industrial production. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing Sv-SnS2 materials based on glucose reduction. The preparation method of the present invention increases the concentration of S vacancies in the SnS2 system, improves its electronic structure, improves the response / recovery performance of the gas sensor, and obtains excellent gas selectivity through the reducing effect of glucose on SnS2. The preparation method of the present invention has low cost, easy operation, high yield, and the prepared Sv-SnS2 material has a large specific surface area.
[0006] The second object of the present invention is to provide Sv-SnS2 material prepared by the above preparation method.
[0007] The third object of the present invention is to provide an application of the Sv-SnS2 material prepared by the above preparation method. The Sv-SnS2 material is used to prepare an ammonia sensor, and the prepared ammonia sensor has a small size, low power consumption, fast response recovery speed at room temperature, excellent applicable conditions, and good detection performance for ammonia.
[0008] In order to achieve the above object, the present invention adopts the following technical solution: The present invention provides a preparation method of Sv-SnS2 material based on glucose reduction, comprising the steps of subjecting a tin source and a solution of thioacetamide to a first hydrothermal reaction to obtain SnS2 powder, mixing the SnS2 powder, water, a cationic surfactant and glucose to obtain a suspension, stirring to obtain a mixed solution, and subjecting the mixed solution to a second hydrothermal reaction to obtain the Sv-SnS2 material.
[0009] The preparation method of the present invention first uses a tin source and thioacetamide as raw materials, obtains SnS2 powder through a first hydrothermal reaction, and then performs a second hydrothermal reaction on a mixed solution containing SnS2 powder, water, a cationic surfactant, and glucose to obtain a Sv-SnS2 material. Since SnS2 is insoluble in water, a cationic surfactant is added to enhance the activity of SnS2 in water and improve the ionization degree of SnS2 in water; SnS2 glucose is decomposed into corresponding organic acids at high temperature, and the S generated by the ionization of SnS2 2- Combined with the above, the S content in the system is reduced, S vacancies are generated at the same time, and the electronic structure of the generated Sv-SnS2 is reduced. The carrier activity in the system is enhanced, the electron transfer efficiency is improved, and it is beneficial to the response recovery of the gas sensor.
[0010] In a preferred embodiment, the solvent in the solution containing the tin source and thioacetamide is anhydrous ethanol.
[0011] In the present invention, anhydrous ethanol is used as the solvent for the preparation of SnS2 powder, and nano-spherical flower-shaped SnS2 powder can be formed. After the raw materials of the present invention are subjected to the second step hydrothermal reaction, the nano-spherical flower-shaped morphology can continue to be maintained. The generated spherical flower-shaped Sv-SnS2 has a large specific surface area, and the spatial stacking structure is conducive to the adsorption of gas, which is very helpful for improving the performance of the sensor.
[0012] The inventors found that the solvent directly affects the formation of the flower-like morphology of the nanospheres. If water is used as the solvent, a lamellar structure of Sv-SnS2 will be obtained, which will reduce the specific surface area of Sv-SnS2.
[0013] In a preferred embodiment, the tin source is selected from tin tetrachloride pentahydrate (SnCl4·5H2O).
[0014] In a preferred embodiment, in the solution containing the tin source and thioacetamide, the concentration of the tin source is 0.02-0.09 mol / L, preferably 0.04-0.08 mol / L, and more preferably 0.061-0.062 mol / L.
[0015] In a preferred embodiment, in the solution containing tin source and thioacetamide, the molar ratio of tin source to thioacetamide is 1:1.8-2.2, preferably 1.9-2.1.
[0016] In a preferred embodiment, the preparation process of the solution containing the tin source and thioacetamide is as follows: the tin source is dissolved in anhydrous ethanol, and then thioacetamide is added, and stirred at a stirring rate of 600-800 r / min for 0.5-0.8 h at room temperature to obtain a colorless transparent solution. The solution containing the tin source and thioacetamide is then transferred to a polytetrafluoroethylene liner for hydrothermal reaction.
[0017] In a preferred embodiment, the temperature of the first hydrothermal reaction is 180-185° C., and the time of the hydrothermal reaction is 16.-16.5 h.
[0018] In a preferred embodiment, after the first hydrothermal reaction is completed, the obtained reaction solution is centrifuged, and the obtained solid phase is vacuum dried to obtain SnS2 powder.
[0019] Further preferably, the centrifugal speed is 5000-5500 r / min.
[0020] Further preferably, the vacuum drying temperature is 60-80° C., and the vacuum drying time is 8-8.5 h.
[0021] In the actual operation process, anhydrous ethanol is centrifuged 3 to 4 times at room temperature to obtain a yellow precipitate, which is then dried in a vacuum drying oven.
[0022] In a preferred embodiment, the concentration of SnS2 powder in the mixed solution is 0.01-0.03 mol / L, preferably 0.021-0.023 mol / L.
[0023] The inventors found that the concentration of the precursor will affect the generated SnS2. The concentration of the original S vacancies in SnS2 generated by precursors of different concentrations is different. When the concentration is controlled within the above range, the performance of the resulting Sv-SnS2 material is optimal.
[0024] In a preferred embodiment, the cationic surfactant is cetyltrimethylammonium bromide (CTAB).
[0025] In a preferred embodiment, in the mixed solution, the molar ratio of SnS2 powder to cationic surfactant is 1:0.01-1.5, preferably 0.8-1.2, and more preferably 0.99-1.01. The inventors found that the amount of cationic surfactant is related to the electrolysis degree of the SnS2 system. Too much cationic surfactant will lead to excessive electrolysis, which may lead to the generation of other substances; too little cationic surfactant may not be enough to enhance the activity of SnS2 in water, and ionization is insufficient.
[0026] In a preferred embodiment, in the mixed solution, in molar ratio, SnS2 powder: C6H 12 O6=1: 0.01-2, preferably 0.2-1.2, and more preferably 0.5-1.02. The inventors found that glucose is a key reagent in the entire reduction process, which is directly related to the concentration of defects and its addition amount needs to be effectively controlled. If the amount of glucose added is too little, too little S defect is generated, and the performance improvement is limited. If the amount of glucose is excessive, SnS2 will be over-corroded, directly changing its original chemical structure, which will also lead to a decrease in performance.
[0027] According to a preferred embodiment, the suspension is obtained by sequentially adding SnS2 powder, a cationic surfactant and glucose into water.
[0028] In a preferred embodiment, the stirring rate is 600-800 r / min, and the stirring time is 2-2.2 h.
[0029] After taking SnS2 powder, cationic surfactant and glucose according to the designed composition and adding them into water, it is crucial to stir them, because stirring can not only make the materials mix more evenly, but more importantly, stirring can enhance the degree of ionization of SnS2. At the same time, using a faster stirring speed within the scope of the present invention will result in an intercalation process, which will cause peeling between atomic layers, thinning the two-dimensional material and further improving the gas-sensitive response.
[0030] In a preferred embodiment, the temperature of the second hydrothermal reaction is 180-185°C, and the time of the second hydrothermal reaction is 12h-12.5h. During the second hydrothermal reaction, the temperature is controlled within the scope of the present invention, and glucose is decomposed into corresponding organic acids at high temperature, taking away S in the system. 2- Generate S defects. Too low temperature will cause glucose to fail to decompose, and too high temperature may change the original structure of SnS2.
[0031] In a preferred embodiment, after the second reaction is completed, the obtained reaction solution is centrifuged and the obtained solid phase is vacuum dried to obtain the Sv-SnS2 material.
[0032] Further preferably, the centrifugal speed is 5000-5500 r / min.
[0033] Further preferably, the vacuum drying temperature is 60-80° C., and the vacuum drying time is 8-8.5 h.
[0034] In the actual operation process, after the reaction is completed, the reaction solution is taken out, and after it is cooled to room temperature, it is centrifuged 3-4 times with deionized water and anhydrous ethanol solution respectively to obtain a brown precipitate, which is then placed in a vacuum drying oven to dry.
[0035] The present invention also provides Sv-SnS2 material prepared by the above preparation method.
[0036] The present invention also provides an application of the Sv-SnS2 material prepared by the above preparation method, and the Sv-SnS2 material is used to prepare an ammonia sensor.
[0037] According to a preferred embodiment, the preparation method of the ammonia sensor is as follows: grind the Sv-SnS2 material for 8-10 min to obtain a powdered material, drop anhydrous ethanol into the powdered material, and grind for another 8-10 min to obtain a slurry, coat the slurry on an Al2O3 substrate with Au metal interdigital electrodes, and perform aging treatment; the aging treatment temperature is 60-80°C, and the aging treatment time is 2-3h.
[0038] Aging is a necessary step for resistive gas sensors, which plays a role in stabilizing the baseline resistance and can reduce the signal-to-noise ratio during the test process. The aging temperature and time are controlled within the scope of the present invention, and the performance of the ammonia sensor finally obtained is optimal. If the aging conditions are unreasonable, the response value of the sensor may be unstable. The aging time process will put SnS2 at risk of oxidation and reduce the S defects in the system.
[0039] In the actual operation process, the Sv-SnS2 material is placed in a mortar and ground for 8-10 minutes to obtain a powdered material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in a 60°C oven and heated for 2 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0040] Principles and advantages The preparation method of the present invention first uses a tin source and thioacetamide as raw materials, obtains SnS2 powder through a first hydrothermal reaction, and then performs a second hydrothermal reaction on a mixed solution containing SnS2 powder, water, a cationic surfactant, and glucose to obtain a Sv-SnS2 material. Since SnS2 is insoluble in water, a cationic surfactant is added to enhance the activity of SnS2 in water and improve the ionization degree of SnS2 in water; SnS2 glucose is decomposed into corresponding organic acids at high temperature, and the S generated by the ionization of SnS2 2- Combine and take away S in the system 2- S defects are generated, and the electronic structure of the generated Sv-SnS2 is reduced in the above manner. The carrier activity in the system is enhanced, and the electron transfer efficiency is improved, which is beneficial to the response recovery of the gas sensor.
[0041] Compared with the prior art, the present invention has at least the following advantages: 1. The present invention uses a liquid phase reduction method to achieve defect introduction of two-dimensional layered materials, which has the characteristics of environmentally friendly raw materials, low production cost, and simple preparation process. It is a defect introduction method suitable for large-scale green production; 2. The Sv-SnS2 nanomaterial prepared by the present invention improves the electronic structure in the two-dimensional SnS2 nanomaterial system, overcoming the application limitation of the inherent poor properties of metal sulfides at low temperatures. The ammonia gas sensor prepared using Sv-SnS2 nanomaterial has a response / recovery time of 13 / 167s under working conditions of 25°C and 30%RH, and has excellent selective performance. The prepared ammonia gas sensor has a small size, low power consumption, fast response recovery speed at room temperature, excellent applicable conditions, and good detection performance for ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the XRD diagram of the 0.15-SG material obtained in Example 1 of the present invention.
[0043] Figure 2 This is the SEM image of the 0.15-SG material obtained in Example 1 of the present invention.
[0044] Figure 3This is the EPR diagram of the Sv-SnS2 material obtained in Examples 1-4 of the present invention.
[0045] Figure 4 Response / recovery diagram of the high-performance ammonia sensor prepared in Examples 1-4 of the present invention.
[0046] Figure 5 Selectivity diagram of the high-performance ammonia sensor obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The present invention is further described below by means of specific examples.
[0048] Example 1
[0049] 1. Preparation of SnS2 powder 80 mL of ethanol solution was measured, and 0.7513 g of tin tetrachloride pentahydrate was weighed and dissolved in the above solution to obtain solution A; then 1.7315 g of thioacetamide was weighed and dissolved in solution A to obtain solution B; solution B was stirred at 500 r / min at 25°C for 30 min to obtain a colorless and transparent solution C, and then solution C was transferred to a polytetrafluoroethylene liner and hydrothermally reacted for 16 h; after the reaction time was completed, the reactor was taken out, and after cooling, it was centrifuged 3 times with anhydrous ethanol at 5000 r / min at room temperature to obtain a yellow precipitate, which was dried in a vacuum drying oven at 60°C for 8 h to obtain powder D, which was SnS2 powder; Preparation of Sv-SnS2 materials 50 mL of deionized water was measured and 0.2011 g of D powder was weighed to obtain a yellow suspension E; then 0.4 g of CTAB was weighed and added to E to obtain a yellow precipitation solution F; then 0.15 g (the molar ratio of glucose to SnS2 powder was 1:0.763) of glucose reagent was weighed and added to F, and the solution was stirred at 600 r / min for 2 h to obtain a yellow solution, which was then transferred to polytetrafluoroethylene for hydrothermal reaction for 12 h; after the reaction was completed, it was taken out, cooled to room temperature, and then centrifuged three times with deionized water and anhydrous ethanol solution at 5000 r / min respectively to obtain a brown precipitate, which was then placed in a vacuum drying oven and dried at 60 ° C for 8 h; the obtained Sv-SnS2 material was marked as 0.15-SG material.
[0050] 3. Preparation of ammonia sensor The prepared Sv-SnS2 two-dimensional sheet structure material is placed in a mortar and ground for 8-10 minutes to obtain a powdery material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in an oven at 60°C and heated for 2 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0051] Example 2
[0052] 1. Preparation of SnS2 powder 80 mL of ethanol solution was measured, and 0.7513 g of tin tetrachloride pentahydrate was weighed and dissolved in the above solution to obtain solution A; then 1.7315 g of thioacetamide was weighed and dissolved in solution A to obtain solution B; solution B was stirred at 500 r / min for 30 min at 25°C to obtain a colorless and transparent solution C, and then solution C was transferred to a polytetrafluoroethylene liner and hydrothermally reacted for 16 h; after the reaction time was completed, the reactor was taken out, and after cooling, it was centrifuged 3 times with anhydrous ethanol at 5000 r / min at room temperature to obtain a yellow precipitate, which was dried in a vacuum drying oven at 60°C for 8 h to obtain powder D, which was SnS2 powder; 2. Preparation of Sv-SnS2 materials 50 mL of deionized water was measured and 0.2011 g of D powder was weighed to obtain a yellow suspension E; then 0.4 g of CTAB was weighed and added to E to obtain a yellow precipitation solution F; then 0.05 g (the molar ratio of glucose to SnS2 powder was 1:0.255) of glucose reagent was weighed and added to F, and the solution was stirred at 600 r / min for 2 h to obtain a yellow solution, which was then transferred to polytetrafluoroethylene for hydrothermal reaction for 12 h; after the reaction was completed, it was taken out, cooled to room temperature, and then centrifuged three times with deionized water and anhydrous ethanol solution at 5000 r / min respectively to obtain a brown precipitate, which was then placed in a vacuum drying oven and dried at 60 ° C for 8 h; the obtained Sv-SnS2 material was marked as 0.05-SG material.
[0053] 3. Preparation of ammonia sensor The prepared Sv-SnS2 two-dimensional sheet structure material is placed in a mortar and ground for 8-10 minutes to obtain a powdery material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in an oven at 60°C and heated for 2 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0054] Example 3
[0055] 1. Preparation of SnS2 powder 80 mL of ethanol solution was measured, and 0.7513 g of tin tetrachloride pentahydrate was weighed and dissolved in the above solution to obtain solution A; then 1.7315 g of thioacetamide was weighed and dissolved in solution A to obtain solution B; solution B was stirred at 500 r / min at 25°C for 30 min to obtain a colorless and transparent solution C, and then solution C was transferred to a polytetrafluoroethylene liner and hydrothermally reacted for 16 h; after the reaction time was completed, the reactor was taken out, and after cooling, it was centrifuged 3 times with anhydrous ethanol at 5000 r / min at room temperature to obtain a yellow precipitate, which was dried in a vacuum drying oven at 60°C for 8 h to obtain powder D, which was SnS2 powder; 2. Preparation of Sv-SnS2 materials 50 mL of deionized water was measured and 0.2011 g of D powder was weighed to obtain a yellow suspension E; then 0.4 g of CTAB was weighed and added to E to obtain a yellow precipitation solution F; then 0.1 g (the molar ratio of glucose to SnS2 powder was 1:0.509) of glucose reagent was weighed and added to F, and the solution was stirred at 600 r / min for 2 h to obtain a yellow solution, which was then transferred to polytetrafluoroethylene for hydrothermal reaction for 12 h; after the reaction was completed, it was taken out, cooled to room temperature, and then centrifuged three times with deionized water and anhydrous ethanol solution at 5000 r / min respectively to obtain a brown precipitate, which was then placed in a vacuum drying oven and dried at 60 ° C for 8 h; the obtained Sv-SnS2 material was marked as 0.1-SG material.
[0056] 3. Preparation of ammonia sensor The prepared Sv-SnS2 two-dimensional sheet structure material is placed in a mortar and ground for 8-10 minutes to obtain a powdery material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in an oven at 60°C and heated for 2 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0057] Example 4
[0058] Preparation of SnS2 powder 80 mL of ethanol solution was measured, and 0.7513 g of tin tetrachloride pentahydrate was weighed and dissolved in the above solution to obtain solution A; then 1.7315 g of thioacetamide was weighed and dissolved in solution A to obtain solution B; solution B was stirred at 500 r / min for 30 min at 25°C to obtain a colorless and transparent solution C, and then solution C was transferred to a polytetrafluoroethylene liner and hydrothermally reacted for 16 h; after the reaction time was completed, the reactor was taken out, and after cooling, it was centrifuged 3 times with anhydrous ethanol at 5000 r / min at room temperature to obtain a yellow precipitate, which was dried in a vacuum drying oven at 60°C for 8 h to obtain powder D, which was SnS2 powder; 2. Preparation of Sv-SnS2 materials 50 mL of deionized water was measured and 0.2011 g of D powder was weighed to obtain a yellow suspension E; then 0.4 g of CTAB was weighed and added to E to obtain a yellow precipitation solution F; then 0.2 g of glucose (the molar ratio of glucose to SnS2 powder is 1:1.018) was weighed and added to F, and the solution was stirred at 600 r / min for 2 h to obtain a yellow solution, which was then transferred to polytetrafluoroethylene for hydrothermal reaction for 12 h; after the reaction was completed, it was taken out, cooled to room temperature, and then centrifuged three times with deionized water and anhydrous ethanol solution at 5000 r / min respectively to obtain a brown precipitate, which was then placed in a vacuum drying oven and dried at 60 ° C for 8 h; the obtained Sv-SnS2 material was marked as 0.2-SG material.
[0059] 3. Preparation of ammonia sensor The prepared Sv-SnS2 two-dimensional sheet structure material is placed in a mortar and ground for 8-10 minutes to obtain a powdery material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in an oven at 60°C and heated for 2 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0060] Performance Testing of Embodiments Figure 1 This is the XRD pattern of the 0.15-SG material obtained in Example 1 of the present invention. Figure 1 We can see that its characteristic peaks correspond well to the PDF (JCPDS 23-0677) card, indicating the successful preparation of the sample. The 2θ values of 15.02, 28.2, and 32.1 correspond to the (001), (100), and (101) crystal planes of SnS2, respectively.
[0061] Figure 2 This is the SEM image of the 0.15-SG material obtained in Example 1. Figure 2It can be seen that 0.15-SG is still in the shape of a nanosphere flower as a whole, and there is erosion at its edges. These eroded edges contain a large number of dangling bonds, which is beneficial to improving the activity of the SnS2 basal plane and is of great help in improving the performance of gas sensors.
[0062] Figure 3 EPR graphs of the Sv-SnS2 materials obtained in Examples 1-4 and the SnS2 powder in Example 1. Figure 3 It is shown that there is a strong signal at g=2.003, confirming that it contains abundant sulfur vacancies. Figure 3 It can be seen that different amounts of glucose added will result in different signal intensities, indicating that the amount of glucose plays a decisive role in the defect concentration, among which the concentration of S vacancies in the 0.15-GS sample is the highest.
[0063] Figure 4 Response / recovery diagram of the high performance ammonia sensor obtained in Examples 1-4 of the present invention. Figure 4 It is shown in the results that the 0.15-SG sensor has a response recovery time of 13 / 167s at room temperature. The reduced Sv-SnS2 sensor overcomes the defect that the SnS2-based sensor is difficult to recover at room temperature, providing an experimental basis for subsequent applications. Figure 4 It can be seen that the performance of 0.15-SG sensor is the best compared with other materials, which is proportional to the defect concentration contained in it.
[0064] Figure 5 Selectivity diagram of a high-performance ammonia sensor made from the 0.15-SG material obtained in Example 1 of the present invention. Figure 5 It is shown in the figure that the 0.15-SG sensor has excellent selectivity at room temperature. Under the same concentration conditions, its response value to ammonia is 7-10 times that of other gases.
[0065] Comparative Example 1 80 mL of ethanol solution was measured, and 0.753 g of tin tetrachloride pentahydrate was weighed and dissolved in the above solution to obtain solution A; then 1.7315 g of thioacetamide was weighed and dissolved in solution A to obtain solution B; solution B was stirred at 500 r / min at 25° C. for 30 min to obtain a colorless and transparent solution C, and then solution C was transferred to a polytetrafluoroethylene liner and hydrothermally reacted for 16 h; after the reaction time was completed, the reactor was taken out, and after cooling, it was centrifuged 3 times with anhydrous ethanol at 5000 r / min at room temperature to obtain a yellow precipitate, which was dried in a vacuum drying oven at 60° C. for 8 h to obtain a D powder; 50 mL of deionized water was measured, and 0.2011 g of D powder was weighed to obtain a yellow suspension E; then 0.1 g of CTAB was weighed and added to E to obtain a yellow precipitation solution F; then 0.15 g of glucose reagent was weighed and added to F, and the solution was stirred at 200 r / min for 1 h to obtain a yellow solution, which was then transferred to polytetrafluoroethylene for hydrothermal reaction for 12 h; after the reaction was completed, it was taken out, cooled to room temperature, and centrifuged three times with deionized water and anhydrous ethanol solution at 5000 r / min respectively to obtain a brown precipitate, which was then placed in a vacuum drying oven and dried at 60°C for 8 h; The prepared Sv-SnS2 two-dimensional sheet structure material is placed in a mortar and ground for 8-10 minutes to obtain a powdery material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in an oven at 60°C and heated for 2 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0066] The stirring speed of the reduction process in the second step of this comparative example 1 is too slow, and the final ammonia sensor is much weaker than that of Example 1. This is because the stirring process can fully combine the reagents, which plays a key role in the ionization of SnS2 and improves the hierarchical nature of S vacancy formation. Furthermore, adding CTAB and stirring it fully can play an intercalation role on the two-dimensional layered material and increase the interlayer spacing of the two-dimensional material. Both aspects are very helpful to the gas-sensitive performance of the gas sensor.
[0067] Comparative Example 2 80 mL of ethanol solution was measured, and 0.753 g of tin tetrachloride pentahydrate was weighed and dissolved in the above solution to obtain solution A; then 1.7315 g of thioacetamide was weighed and dissolved in solution A to obtain solution B; solution B was stirred at 500 r / min at 25° C. for 30 min to obtain a colorless and transparent solution C, and then solution C was transferred to a polytetrafluoroethylene liner and hydrothermally reacted for 16 h; after the reaction time was completed, the reactor was taken out, and after cooling, it was centrifuged 3 times with anhydrous ethanol at 5000 r / min at room temperature to obtain a yellow precipitate, which was dried in a vacuum drying oven at 60° C. for 8 h to obtain a D powder; 50 mL of deionized water was measured, and 0.2011 g of D powder was weighed to obtain a yellow suspension E; then 0.1 g of CTAB was weighed and added to E to obtain a yellow precipitation solution F; then 0.15 g of glucose reagent was weighed and added to F, and the solution was stirred at 600 r / min for 2 h to obtain a yellow solution, which was then transferred to polytetrafluoroethylene for hydrothermal reaction for 12 h; after the reaction was completed, it was taken out, cooled to room temperature, and centrifuged three times with deionized water and anhydrous ethanol solution at 5000 r / min to obtain a brown precipitate, which was then placed in a vacuum drying oven and dried at 60°C for 8 h; The prepared Sv-SnS2 two-dimensional sheet structure material is placed in a mortar and ground for 8-10 minutes to obtain a powdery material; then anhydrous ethanol is dripped into the mortar and ground for another 8-10 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and evenly coated on an Al2O3 substrate with Au metal interdigital electrodes, and then placed in a 90°C oven and heated for 5 hours for aging treatment to obtain an ammonia sensor of Sv-SnS2 spherical flower-shaped nanomaterials.
[0068] The ammonia sensor obtained in this example is significantly lower than that in Example 1, because the aging temperature and time of the sensor in Comparative Example 2 are very critical. The aging process is accompanied by heating, and the defect-rich Sv-SnS2 gas sensor may have an oxidation risk. Too high temperature or too long aging time may affect the content of S defects, which affects the activity of the sensor sensitive layer at room temperature.
[0069] Finally, it should be noted that the above examples are only specific implementation examples of the present invention. Obviously, the present invention is not limited to the above examples, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing Sv-SnS2 material based on glucose reduction, characterized in that: The solution containing the tin source and thioacetamide is subjected to a first hydrothermal reaction to obtain SnS2 powder, the SnS2 powder, water, a cationic surfactant, and glucose are mixed to obtain a suspension, and then stirred to obtain a mixed solution, and the mixed solution is subjected to a second hydrothermal reaction to obtain Sv-SnS2 material.
2. The method for preparing a Sv-SnS2 material based on glucose reduction according to claim 1, characterized in that: The solvent in the solution containing the tin source and thioacetamide is anhydrous ethanol.
3. A method for preparing a Sv-SnS2 material based on glucose reduction according to claim 1 or 2, characterized in that: The tin source is selected from tin tetrachloride pentahydrate; In the solution containing tin source and thioacetamide, the concentration of tin source is 0.02-0.09 mol / L; In the solution containing tin source and thioacetamide, the molar ratio of tin source to thioacetamide is 1:1.8-2.2; The preparation process of the solution containing the tin source and thioacetamide is as follows: dissolving the tin source in anhydrous ethanol, then adding thioacetamide, and stirring at a stirring rate of 600-800 r / min for 0.5-0.8 h at room temperature to obtain a colorless and transparent solution.
4. A method for preparing a Sv-SnS2 material based on glucose reduction according to claim 1 or 2, characterized in that: The temperature of the first hydrothermal reaction is 180-185°C, and the time of the hydrothermal reaction is 16.-16.5h; After the first hydrothermal reaction is completed, the reaction solution is centrifuged and the solid phase is vacuum dried to obtain SnS2 powder; the centrifugal speed is 5000-5500r / min; the vacuum drying temperature is 60-80°C and the vacuum drying time is 8-8.5h.
5. The method for preparing a Sv-SnS2 material based on glucose reduction according to claim 1, characterized in that: In the mixed solution, the concentration of SnS2 powder is 0.01-0.03 mol / L.
6. The cationic surfactant is CTAB, In the mixed solution, the molar ratio of SnS2 powder to cationic surfactant is 1:0.01-1.5; In the mixed solution, based on molar ratio, SnS2 powder:C6H 12 O6=1:0.01-2.
7. A method for preparing a Sv-SnS2 material based on glucose reduction according to claim 1 or 5, characterized in that: The suspension is obtained by sequentially adding SnS2 powder, cationic surfactant and glucose into water; The stirring rate is 600-800 r / min, and the stirring time is 2-2.2 h.
8. The method for preparing a Sv-SnS2 material based on glucose reduction according to claim 1, characterized in that: The temperature of the second hydrothermal reaction is 180-185°C, and the time of the second hydrothermal reaction is 12 h-12.5 h; After the second reaction is completed, the obtained reaction solution is centrifuged, and the obtained solid phase is vacuum dried to obtain Sv-SnS2 material; The centrifugal speed is 5000-5500r / min; The vacuum drying temperature is 60-80° C., and the vacuum drying time is 8-8.5 h.
9. Sv-SnS2 material prepared by the preparation method described in any one of claims 1-8.
10. Application of the Sv-SnS2 material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Sv-SnS2 material is used to prepare an ammonia sensor; the preparation method of the ammonia sensor is as follows: grind the Sv-SnS2 material for 8-10 min to obtain a powder material, drip anhydrous ethanol into the powder material, grind it for another 8-10 min to obtain a slurry, coat the slurry on an Al2O3 substrate with Au metal interdigital electrodes, and perform aging treatment; the aging treatment temperature is 60-80°C, and the aging treatment time is 2-3h.
Citation Information
Patent Citations
Preparation method of SnS2 ultrathin nanosheet rich in S vacancy sites
CN107814408A
Preparation of SnS2 nanosheet with S vacancy and application of SnS2 nanosheet in photodegradation of Cr (VI)
CN112495400A
CdS-coated SnS2 composite material for photocatalysis as well as preparation method and application thereof
CN112619668A
SnS2 microsphere SERS substrate with capillary effect as well as preparation method and application of SnS2 microsphere SERS substrate
CN113484302A
Visible light modulated high-selectivity NO2 gas sensor based on Au / SnS2 nano composite material and preparation method of visible light modulated high-selectivity NO2 gas sensor
CN115974135A